2013
DOI: 10.1016/j.supflu.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Wound dressings loaded with an anti-inflammatory jucá (Libidibia ferrea) extract using supercritical carbon dioxide technology

Abstract: a b s t r a c t N-Carboxybutyl chitosan (CBC), collagen/cellulose (Promogran ® ) and hyaluronic acid-based (Hyalofill ® ) polymeric matrices/dressings were loaded with an extract obtained from jucá (Libidibia ferrea) and in order to develop wound dressings endowed with anti-inflammatory activity. Jucá fruits were subjected to supercritical fluid extraction (SFE) using CO 2 at 25 MPa and 50• C and the resulting extract was later incorporated into the above referred wound dressings by a supercritical fluid impre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 87 publications
0
55
1
3
Order By: Relevance
“…On the contrary is noticed for hydrophobic compounds that prefer polymers with long alkyl-chains and presenting a strong hydrophobicity [36,85,86]. For example, hydrophobic extracts from juca fruits were found to be more loaded into N-carboxybutyl chitosan than into two other commercial dressings due to its higher hydrophobicity and to favorable interactions, thus increasing the partitioning coefficient of the molecules in this matrix [36]. In case of hydrogels, the presence of water in the matrix hinders the impregnation of hydrophobic drugs that prefer to stay in the scCO 2 phase [32].…”
Section: {Polymer + Api}: Affinitymentioning
confidence: 97%
See 3 more Smart Citations
“…On the contrary is noticed for hydrophobic compounds that prefer polymers with long alkyl-chains and presenting a strong hydrophobicity [36,85,86]. For example, hydrophobic extracts from juca fruits were found to be more loaded into N-carboxybutyl chitosan than into two other commercial dressings due to its higher hydrophobicity and to favorable interactions, thus increasing the partitioning coefficient of the molecules in this matrix [36]. In case of hydrogels, the presence of water in the matrix hinders the impregnation of hydrophobic drugs that prefer to stay in the scCO 2 phase [32].…”
Section: {Polymer + Api}: Affinitymentioning
confidence: 97%
“…Natu et al have shown that timolol maleate which is a hydrophilic drug is more impregnated in poly(ε-caprolactone) PCL blended with poly(oxyethylene-b-oxypropylene-b-oxyethylene) (PCL/POE) copolymer than in PCL blended with poly(ethylene-co-vinyl acetate) (PCL/ PEVA) copolymer because of the higher hydrophilicity of the first copolymer [44]. On the contrary is noticed for hydrophobic compounds that prefer polymers with long alkyl-chains and presenting a strong hydrophobicity [36,85,86]. For example, hydrophobic extracts from juca fruits were found to be more loaded into N-carboxybutyl chitosan than into two other commercial dressings due to its higher hydrophobicity and to favorable interactions, thus increasing the partitioning coefficient of the molecules in this matrix [36].…”
Section: {Polymer + Api}: Affinitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among the chemical components described in the literature for the genus Libidibia the presence of polyphenols is highlighted. Another class of substances that have been characterized are terpenoids, which are usually extracted with low polarity solvents (Dias et al 2013). …”
Section: Discussionmentioning
confidence: 99%